Pharmacogenomic and in silico identification of isoform-selective AKT inhibitors from Pithecellobium dulce for precision cancer therapy - Jeyaraj, Gnanaprakash; Yang, Bing; Sathishkumar, Kuppusamy; Chokkakula, Santosh; Almutairi, Bader O.; Xie, Weimim (Frontiers in Pharmacology, 2026)
ObjectiveAKT1 and AKT2 are central but functionally distinct kinases within the PI3K–AKT–mTOR pathway, and isoform‐specific genomic alterations in these proteins have important implications for cancer prognosis and therapeutic responsiveness. This study aimed to integrate cancer pharmacogenomics with structure‐based modeling to identify natural compounds capable of selectively targeting AKT1 or AKT2.MethodsPublic cancer genomics datasets from TCGA and the Kaplan–Meier Plotter were analyzed to characterize mutation patterns, copy number alterations, and survival associations of AKT1 and AKT2 across malignancies. Based on isoform-specific differences, twenty phytochemicals from Pithecellobium dulce were docked against the allosteric binding sites of AKT1 (PDB: 3QKL) and AKT2 (PDB: 2JDO). Lead compounds were evaluated using ADME prediction and density functional theory to assess pharmacokinetic suitability and electronic stability. The dynamic behavior of ligand–protein complexes was examined through 200‐ns molecular dynamics simulations using the Desmond–Schrödinger platform, and binding free energies were estimated via MM‐GBSA analysis. Regulatory interactions involving AKT‐associated non‐coding RNAs were also examined to support pharmacogenomic relevance.ResultsGenomic analysis revealed that AKT1 alterations were dominated by activating missense mutations, particularly the E17K hotspot, whereas AKT2 showed frequent gene amplifications that were significantly associated with poor overall survival. Docking studies demonstrated clear isoform selectivity among P. dulce phytochemicals: oleanolic acid and pitheduloside I preferentially bound AKT1, while rutin and naringin exhibited stronger affinity toward AKT2. Oleanolic acid and rutin displayed binding energies comparable to established allosteric AKT inhibitors. ADME and DFT analyses supported favorable drug‐likeness and molecular stability of the lead compounds. Molecular dynamics simulations confirmed stable complex formation with persistent hydrogen bonding, and MM‐GBSA calculations indicated superior binding energetics for oleanolic acid–AKT1 and rutin–AKT2 complexes relative to controls. In parallel, analysis of miR-149‐5p and lncRNA HOTAIR highlighted post‐transcriptional regulatory mechanisms influencing AKT isoform activity.ConclusionThis study demonstrates that integrating pharmacogenomic profiling with multiscale molecular simulations can reveal isoform‐specific vulnerabilities within the AKT signaling axis. Phytochemicals derived from Pithecellobium dulce, particularly oleanolic acid and rutin, emerge as promising selective modulators of AKT1 and AKT2, respectively. These findings provide a mechanistic and structural foundation for the development of isoform‐guided AKT‐targeted therapies and support further experimental validation toward precision oncology applications.